2016
DOI: 10.3389/fpls.2016.01675
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Differences in DNA Methylation Changes in Two Contrasting Rice Genotypes in Response to Drought Conditions

Abstract: Differences in drought stress tolerance within diverse rice genotypes have been attributed to genetic diversity and epigenetic alterations. DNA methylation is an important epigenetic modification that influences diverse biological processes, but its effects on rice drought stress tolerance are poorly understood. In this study, methylated DNA immunoprecipitation sequencing and an Affymetrix GeneChip rice genome array were used to profile the DNA methylation patterns and transcriptomes of the drought-tolerant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 54 publications
12
85
0
Order By: Relevance
“…However, studies using a limited number of rice genotypes exhibited inconsistent results. E.g., one study reported very similar general methylation levels between DK151 (tolerant genotype) and IR64 (susceptible genotype) (Wang et al, 2011), while other studies reported lower DNA methylation levels or hypo-methylation in drought-tolerant genotypes under both normal and stressed conditions (Gayacharan and Joel, 2013; Zheng et al, 2013; Wang W. et al, 2016). These inconsistent results are suggested to be due to genotype-specific manners of DNA methylation (Karan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, studies using a limited number of rice genotypes exhibited inconsistent results. E.g., one study reported very similar general methylation levels between DK151 (tolerant genotype) and IR64 (susceptible genotype) (Wang et al, 2011), while other studies reported lower DNA methylation levels or hypo-methylation in drought-tolerant genotypes under both normal and stressed conditions (Gayacharan and Joel, 2013; Zheng et al, 2013; Wang W. et al, 2016). These inconsistent results are suggested to be due to genotype-specific manners of DNA methylation (Karan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…E.g., 64212 (N22/IR64) and 35723 (PK/IR64) differentially methylated regions (DMR) were identified between two pairs of different cultivars via whole genome bisulphite sequencing, which covered 57.9 and 38.5% protein coding genes annotated in the reference genome (Garg et al, 2015). Furthermore, large proportions of DMRs detected between two cultivars were reported not stress-relevant, as they were not in response to drought-stress (Wang W. et al, 2016). It is therefore difficult to determine whether these differences in DNA methylation between two genotypes are associated with their contrasting tolerances or merely with a different genetic background.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results indicated that putrescine had the antagonistic effect against picloram. Recently, several studies have indicated that stress positively contributed to tolerance as alter genes expression by DNA methylation and histone modifications (Wang et al, 2016;Feng et al, 2016). In additional, the present study evaluated the protective role of putrescine against picloram genotoxicity.…”
mentioning
confidence: 92%